Discordance in LVEF Between Nuclear SPECT and Echocardiography in Patients With Moderate Reduction in LVEF. (July 2019) - Rawala, Muhammad Shabbir; Memon, Adil; Yasin, Muhammad; Karpe, Vallabh; Brewer, Zachary S.; Harrington, Cecilia V.; Kemper, Suzanne E.; Carter, William H.
Left ventricular ejection fraction (LVEF) is vital to manage heart failure (HF). Studies have reported variable correlations for LVEF between echocardiography (ECHO) and single-photon emission computed tomography (SPECT). A retrospective review of 235 patients was conducted to compare LVEF via ECHO and SPECT done within 72 hours. Mean LVEF by ECHO was 51% and 57% by SPECT. A moderately positive correlation resulted ( r = .76, P ≤ .05) for all, but a weak correlation was noted in 99 with LVEF of 25% to 50% ( r = .43, p≤0.05). Further imaging may be needed for discordant results when medications and/or devices are considered.